Factors Used For Effective Awareness Of Climate Change Among Social Studies Teachers In Delta State. - Sunday, Obro; Dania, P. O. (Advances in Social Sciences Research Journal, 2017)
This study focuses on factors used for effective awareness of climate change among Social Studies teachers in Delta State. Four research questions and four research hypothesis were used for the study. The research design used is a descriptive survey. The population of the study consists of 556 Social studies teachers in Delta State. The sample used is (120) one hundred and twenty Social studies teachers. The multi-stage random sampling technique was adopted for the study. The instrument for the study was the questionnaire tagged “FUEACCQ”. Test re-test method of determining the reliability was used to establish the reliability of the instrument. The Pearson Moment Correlation used to analyse the instrument; it gave a value of 0.78. The z-test statistical tool was used for the analysis of the data collected at 0.05 probability level. The findings revealed that internet facilities enhances climate changes awareness among Social Studies teachers in Delta State; community campaign help in climate change awareness among Social Studies teachers in Delta State; media enhances climate changes awareness among Social Studies teachers in Delta State; seminar/workshop enhances climate changes awareness among Social Studies teachers in Delta State. Based on findings, it is recommended that government should make provisions of internet facilities to enhance climate change awareness among Social Studies teachers in Delta State should be taken seriously to inform the public on the effectiveness of climate change awareness.